2003
DOI: 10.1046/j.1365-2958.2003.03319.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel regulatory gene for light‐induced carotenoid synthesis in the bacteriumMyxococcus xanthus

Abstract: SummaryMyxococcus xanthus cells respond to blue light by producing carotenoids. Light triggers a network of regulatory actions that lead to the transcriptional activation of the carotenoid genes. By screening the colour phenotype of a collection of Tn 5-lac insertion mutants, we have isolated a new mutant devoid of carotenoid synthesis. We map the transposon insertion, which co-segregates with the mutant phenotype, to a previously unknown gene designated here as carF . An in frame deletion within carF causes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
68
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 51 publications
0
68
0
Order By: Relevance
“…Strong genetic evidence indicates that CarF is the earliest acting of all known Car elements of the light-driven regulatory cascade, being absolutely necessary for the lightdependent inactivation of CarR (Fontes et al, 2003). Contrary to all other known Car regulatory proteins, CarF does not take part in the carotenogenic response to copper (Moraleda-Muñoz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Strong genetic evidence indicates that CarF is the earliest acting of all known Car elements of the light-driven regulatory cascade, being absolutely necessary for the lightdependent inactivation of CarR (Fontes et al, 2003). Contrary to all other known Car regulatory proteins, CarF does not take part in the carotenogenic response to copper (Moraleda-Muñoz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The complex regulatory network retained by this unique bacterium involves multiple transcriptional regulators and associated proteins. 1,2) Recently, we found that Streptomyces coelicolor A3(2), a Gram-positive soil bacterium, produces carotenoid when exposed to light. 3) Evidence showed that LitR, a MerR-family protein, serves as a photo-dependent transcriptional regulator for litS, which encodes an ECF family sigma factor that specifies the transcription of carotenoid biosynthesis genes (crt).…”
mentioning
confidence: 99%
“…The cloned DNA fragment contained the litQRS cluster and a flanking promoter region, PcrtY. PcrtY is a LitSdependent promoter that directs the transcription of one of the two operons for carotenoid biosynthesis, crtYTU, in S. coelicolor A3 (2). By the plasmid construction, PcrtY directed the transcription of a promoter-less mel operon that was located downstream from the promoter in the same orientation.…”
mentioning
confidence: 99%
“…Six of these enzymes are encoded by this operon and only one by crtI (14 -16). carF is a recently identified gene whose product has been proposed to function as an anti-anti-factor at the earliest step in the regulatory cascade (17). The carQRS locus is a key regulatory operon that encodes three proteins with low, basal levels of expression in the dark: the extracytoplasmic function -factor CarQ (18 -20), its antifactor CarR (18,20), and the antirepressor protein CarS (21,22).…”
mentioning
confidence: 99%
“…The carQRS locus is a key regulatory operon that encodes three proteins with low, basal levels of expression in the dark: the extracytoplasmic function -factor CarQ (18 -20), its antifactor CarR (18,20), and the antirepressor protein CarS (21,22). Central to the induction of carotenogenesis on exposure to light is the CarF-mediated inactivation of CarR to release CarQ (17,18). Once liberated, CarQ up-regulates expression of car-QRS and crtI (18).…”
mentioning
confidence: 99%